2015
DOI: 10.1111/hex.12359
|View full text |Cite
|
Sign up to set email alerts
|

Association between patient activation and patient‐assessed quality of care in type 2 diabetes: results of a longitudinal study

Abstract: Background Previous research using cross-sectional data has shown a positive relationship between patient activation and quality of care. The quantitative relationships in the same patients over time, however, remain undefined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
23
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 47 publications
10
23
2
Order By: Relevance
“…In fact, our patients' overall score (computed over the 20‐item PACIC) is in agreement with those reported in several other studies. For example, Aung et al, who conducted a population‐based study in Australia including type 2 patients, found a score of 2.4 at baseline . In Denmark, a similar overall score was reported, but, contrary to our study, participants were recruited in primary care practices, yet mean age and sex of participants were similar to our sample .…”
Section: Discussionsupporting
confidence: 53%
“…In fact, our patients' overall score (computed over the 20‐item PACIC) is in agreement with those reported in several other studies. For example, Aung et al, who conducted a population‐based study in Australia including type 2 patients, found a score of 2.4 at baseline . In Denmark, a similar overall score was reported, but, contrary to our study, participants were recruited in primary care practices, yet mean age and sex of participants were similar to our sample .…”
Section: Discussionsupporting
confidence: 53%
“…Way of life intercessions as supper arranging and exercise assume a significant job in a diabetes self-administration instruction program. Achievement in the selfadministration of sort 2 diabetes requires a learning base on the infection course, a comprehension of the impact of significant way of life intercessions, and a patient who is effectively occupied with the administration of their wellbeing [29,30,31]. Persistent actuation was low in those sort 2 diabetes patients with comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to the correlations between the measures and some variables, we verified that only the variable, level of education showed significant correlation with the measure of activation and that the variable of number of comorbidities showed a significant correlation with measure of self-esteem. Studies that analyze the associations between activation of the patient have demonstrated that patients with a higher level of education in health are more activated (SMITH, 2013;AUNG, 2015).…”
Section: Discussionmentioning
confidence: 99%